2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2018
DOI: 10.1109/cvprw.2018.00077
|View full text |Cite
|
Sign up to set email alerts
|

Covariance Pooling for Facial Expression Recognition

Abstract: Classifying facial expressions into different categories requires capturing regional distortions of facial landmarks. We believe that second-order statistics such as covariance is better able to capture such distortions in regional facial features. In this work, we explore the benefits of using a manifold network structure for covariance pooling to improve facial expression recognition. In particular, we first employ such kind of manifold networks in conjunction with traditional convolutional networks for spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 25 publications
(47 reference statements)
1
101
0
2
Order By: Relevance
“…Accuracy # classes D/S Jung et al [18] 74.17 6 Dynamic Kacem et al [20] 83. 13 6 Dynamic Liu et al [41] 74.59 6 Dynamic Guo et al [47] 75.52 6 Dynamic Cai et al [42] 77. 29 6 Static Ding et al [4] 82.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accuracy # classes D/S Jung et al [18] 74.17 6 Dynamic Kacem et al [20] 83. 13 6 Dynamic Liu et al [41] 74.59 6 Dynamic Guo et al [47] 75.52 6 Dynamic Cai et al [42] 77. 29 6 Static Ding et al [4] 82.…”
Section: Methodsmentioning
confidence: 99%
“…The two networks are then combined using a joint fine-tuning method. Acharya et al [13] have extended their static approach discussed before to dynamic facial expression recognition. They considered the temporal evolution of per-frame features by leveraging covariance pooling.…”
Section: Related Workmentioning
confidence: 99%
“…Recent work has shown that similar techniques [7,22,27], learnable generalizations of these techniques [8,48], and efficient approximations to these techniques [16,20] also improve the performance of convolutional networks. The improvement is especially large in fine-grained classification settings, such as facial recognition [4,9,27]. However, using the resulting expanded feature space requires parameter- heavy models, even in the few-shot setting [49].…”
Section: Related Workmentioning
confidence: 99%
“…For hard classification problems, methods such as bilinear pooling [27], fisher vectors [34] and others [4,16,22] can be used to expand the feature space and increase expressive power. Unfortunately, a traditional learning framework uses these expanded representations as input to linear classifiers, fully-connected softmax layers, or multilayer networks [9,20,27,49], dramatically increasing parameters and making the model prone to catastrophic overfitting.…”
Section: Covariance Poolingmentioning
confidence: 99%
See 1 more Smart Citation